PROBLEMS IN MASTERING ANATOMICAL TERMINOLOGY AMONG MEDICAL STUDENTS AND THEIR SOLUTIONS (Universal International Scientific Journal, 2026)
This article analyzes the main difficulties faced by medical students in masteringanatomical terminology. The complexity of Latin and Greek-based anatomical terms, the large volumeof terminology, and insufficient integration of anatomy with clinical disciplines pose significantchallenges in the learning process. The study examines students’ levels of terminological competence,their ability to memorize anatomical terms, and their application in clinical practice. Furthermore, theeffectiveness of traditional and modern teaching approaches in anatomy education is compared. Toaddress the identified problems, the use of visual learning tools, clinical cases, interactive teachingmethods, and digital educational technologies is recommended. The findings of the study contribute tothe development of methodological recommendations aimed at improving the teaching and learning ofanatomical terminology in medical education.
Keywords: anatomical terminology; medical education; latin